Bundle Branch Reentrant Ventricular Tachycardia - Boris Strasberg (Indian Pacing and Electrophysiology Journal, 2005)
Bundle branch reentrant (BBR) tachycardia is an uncommon form of ventricular tachycardia (VT) incorporating both bundle branches into the reentry circuit. The arrhythmia is usually seen in patients with an acquired heart disease and significant conduction system impairment, although patients with structurally normal heart have been described. Surface ECG in sinus rhythm (SR) characteristically shows intraventricular conduction defects. Patients typically present with presyncope, syncope or sudden death because of VT with fast rates frequently above 200 beats per minute. The QRS morphology during VT is a typical bundle branch block pattern, usually left bundle branch block, and may be identical to that in SR. Prolonged His-ventricular (H-V) interval in SR is found in the majority of patients with BBR VT, although some patients may have the H-V interval within normal limits. The diagnosis of BBR VT is based on electrophysiological findings and pacing maneuvers that prove participation of the His- Purkinje system in the tachycardia mechanism. Radiofrequency catheter ablation of a bundle branch can cure BBR VT and is currently regarded as the first line therapy. The technique of choice is ablation of the right bundle. The reported incidence of clinically significant conduction system impairment requiring implantation of a permanent pacemaker varies from 0% to 30%. Long-term outcome depends on the underlying cardiac disease. Patients with poor systolic left ventricular function are at risk of sudden death or death from progressive heart failure despite successful BBR VT ablation and should be considered for an implantable cardiovertor-defibrillator.